Basics Financial Management - Rico Nur Ilham; Irada Sinta; Frengki Putra Ramansyah; M. Faddel; Nuriana (CV. RADJA PUBLIKA, 2025)
Financial management is a managerial function that plays an important role in maintaining sustainability. And increase mark company. Article This aim For study basics management finance as well as his role in taking decision managerial. The discussion focused on draft, function, objective, principle, as well as decision main management finance which includes investment, funding, and dividend decisions. The research method used is the analytical approach. qualitative with studies library through review book text And literature scientific relevant information. The study results show that the implementation of effective and efficient financial management can optimize the use of funds, minimize financial risks, and support the achievement of company goals sustainably. A sound understanding of the fundamentals of financial management provides a crucial foundation for managers in formulating rational and strategic financial policies.